Additional notes on Oreocharis yunnanensis, a species of Gesneriaceae from southern Yunnan, China, including morphological and molecular data - Tan, Yun-Hong; Li, Jian-Wu; Chen, Wen-Hong; Wen, Bin; Möller, Michael (Phytotaxa, 2014)
Oreocharis yunnanensis, a recently described species from southern Yunnan, China, is here compared using morphological and molecular evidence, with its closest congener O. aurea and O. hirsuta, but can be easily distinguished from the latter two by its cordate leaves, 3–4 branched cymes with 4–16(–20) flowers, corolla larger, corolla tube constricted or slightly constricted above the base and then moderately enlarged without constriction at the throat, longer relative to the corolla lip, the upper corolla lip much smaller than the lower lip, lobes entire or calyx margins 2–3 denticulate, disc entire or subentire, and stigma capitate.